P01.017 Geriatric Assessments in Neuro Oncology - a viable prospect - Lorimer, C (Neuro Oncol, 2018)
BACKGROUND: An ageing population brings new challenges for oncologists in the management of older cancer patients. There is increasing use of a geriatric assessment (GA) to evaluate fitness for treatment and identify geriatric syndromes. GAs can predict for chemotherapy toxicity and overall survival however there is a paucity of data within the neuro oncology cohort. A criticism of GAs is that they are time and resource consuming. We conducted a feasibility study to assess whether a GA could be performed by members of the usual clinical staff in a UK NHS neuro oncology outpatient setting. MATERIAL AND METHODS: Patients aged ≥ 65 with a new diagnosis of GBM were prospectively recruited from neuro-oncology outpatient clinics across 3 UK centres. A modified GA was performed by the clinical nurse specialists and demographic, imaging and toxicity data collected. Feasibility was assessed primarily by recruitment rate. Secondary outcomes of completion rate, acceptability to staff and patients and overall survival were measured. After completion of the study, face to face semi-structured interviews with the nurses were performed; these were interpreted qualitatively using thematic analysis. RESULTS: Recruitment to the study completed within the 1 year study time. 22 women and 28 men were enrolled with a mean age of 71 (65–86). Median overall survival was 8.2 months. 41 patients received active treatment (17 palliative radiotherapy, 19 chemo radiation and 5 temozolomide alone). Of the 35 patients who were tested, 31% showed MGMT promoter methylation; no IDH mutations were detected. All centres achieved recruitment rates above the target of 80% (mean 92%, 95% CI 86%-96%). Mean assessment completion rate was 94% (95% CI 92–95%). The nurses reported that completing the assessment was manageable and that, in some cases, underlying patient factors were identified that led to changes in treatment plans. Univariable regression analysis showed the MoCA (HR 2.78, p=0.02), IADLs (HR 2.88, p=0.03), baseline mobility (HR 12.1 p=0.002), ECOG PS (HR 29.2 p=0.003) and level of anxiety (HR 3.5 p=0.001) were related to overall survival, alongside treatment received. Multivariate Cox regression modelling confirmed the MoCA score to be a significant independent predictive factor for overall survival. CONCLUSION: ASCO and SIOG promote the use of a GA in the management of older cancer patients and it is becoming widely used within other tumour groups. However, to the authors’ knowledge, this is the first study of a GA within the neuro oncology patient cohort, a group with its own particular symptom burden. We have shown that performing a GA is feasible within the confines of a busy UK outpatient clinic and that, within the accepted limits of the study size, the results can help predict overall survival irrespective of treatment received. Wider use of a neurologically focussed GA should now be explored with greater patient numbers.